Does Vitamin D3 supplementation affect antioxidant enzymes of D3 deficient patients with asthma COPD overlap (ACO)? - A randomized controlled trial - Mahmud, Maksuda Bintey; Ali, Taskina; Bennoor, Kazi Saifuddin; Hossain, Md Ali; Rahman, Mustafizur; Khan, Mohammad Abdus Shakur; Islam, Md Saiful; Hassan, Samia; Nahar, Salsa Bil; Rosy, Sharkia Khanam; et al. (Journal of Bangladesh Society of Physiologist, 2020)
Background: Asthma COPD overlap (ACO) is a new disease entity where respiratory tract is continuously exposed to oxidants. Supplementation of vitamin D3 have shown evidence of increasing antioxidant enzymes level which neutralize these oxidants. Objectives: To evaluate the effects of vitamin D3 supplementation on two antioxidant enzyme levels in D3 deficient ACO patients. Methods: A double blinded placebo controlled randomized clinical trial (RCT) was carried out on 60 (sixty) D3 deficient [serum 25-hydroxycholecalciferol, 25(OH) D<30 ng/ml], male, smoker, stable ACO patients of age 40 to 80 years. This RCT was registered at www.clinicaltrials.gov identifier NCT03931889. After the final selection, all the patients were randomly allocated to vitamin D3 supplemented ‘Study’ group (n=30) or placebo treated ‘Control’ group (n=30). Two antioxidant enzyme levels [plasma superoxide dismutase (SOD) and catalase (CAT)] were measured at their baseline. Subsequently, along with standard pharmacological treatment of ACO, ‘Study’ patients received 80,000 IU (2 oral capsules) of vitamin D3 per week for first 13 weeks. Thereafter, according to their serum 25(OH)D or calcium concentration, they received 40,000 IU (1 oral capsule) of D3 per 1 week or per 2 weeks or per 6 weeks or no further supplementation, for another 13 weeks. Whereas, all the ‘Control’ patients received two oral capsules of placebo weekly, for consecutive 26 weeks. All patients of both groups were also advised to have sunlight exposure (within 11 am to 4 pm) only for 20 minutes daily. After 26 weeks of follow up, both enzyme levels of all patients were again measured. Both enzymes were measured by ELISA method using spectrophotometry. Data were analyzed by Student’s paired and unpaired ‘t’ test, where p≤0.05 was accepted as significant. Results: Initially a total 60 patients were enrolled and randomized, but ultimately 40 of them completed the trial. The baseline antioxidant enzymes levels of two groups were not significantly different. However, the mean level of both enzymes increased in both groups after 26 weeks of follow up but it was statistically significant (p<0.001) only in ‘Study’ patients. In addition, SOD (p<0.05) and CAT (p<0.01) were significantly higher in the vitamin D3 supplemented patients than those of placebo treated patients after 26 weeks of follow up. Conclusion: The present study reveals that vitamin D3 supplementation increases the antioxidant enzyme level in vitamin D3 deficient stable ACO patients. J Bangladesh Soc Physiol. 2019, December; 14(2): 89-98